Structural and optical properties of Sb doped SnO2 nanopowders synthesized by nebulized spray pyrolysis. (2018) - John Silvister Raju, M.; Bhattacharya, S.S.
Abstract: Nebulized spray pyrolysis (NSP) was used to synthesize Sn1-x O2 : Sbx (x=0, 0.03, 0.06, 0.09) nanopowders in reasonable quantities by making use of low-cost precursors. Structural analysis was carried out by XRD, TEM, SEM and XPS. X-ray diffraction analysis confirmed the formation of phase-pure SnO2 with Sb being incorporated into the crystal structure. Rietveld refinement was used to estimate the lattice parameters and by adopting spherical harmonics, the crystallite sizes were calculated. Transmission electron microscopy revealed that the as-synthesized powders had good crystallinity with particle sizes in the range of 5-15 nm, which was in accordance with crystallite sizes calculated from Rietveld refinement.XPS confirmed the presence of antimony in the doped samples. Optical transparency was evaluated by absorption spectroscopy, which revealed both pure and doped SnO2 to have more than 80% transparency in the visible regime. The band gap energies were estimated from standard Tauc plots.